Lack Evidence of Renal Impairment Complaints among Multiple Sclerosis Patients - Al Gawwam, Gheyath; Emad Mohammed, Ahmed; A. Al-Johar, Zuhair; Abdulmajid Dyab Allawi, Ali; Abdulghani Hammoudi, Faten (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Multiple sclerosis MS is a demyelinated, inflammatory disease. Several researchers referred to the fact that the dysfunction in non-neural tissues plays a crucial role in MS disease pathogenesis. Patients and methods: 150 patients were included in this study. The demographic data has been obtained from all patients, as well as renal function, co-morbidities, and type of MS. Type of drug and bladder symptoms have been recorded. Results: Our results showed that the renal function test was followed (mean ± SD): serum creatinine 0.9 ± 1.6, blood urea 35.2 ± 15.7, and eGFR 111.4 ± 35.2. Co-morbidities: hypertension (20 patients) and diabetes (10 patients). Higher numbers of patients were diagnosed with RRMS (128 patients), and lower numbers were diagnosed with SPMS (5 patients). Most of the patients were using the interferon-beta drug (114 patients). Generally, 55 patients complained of bladder incontinence, 50 patients complained of retention, and 31 patients complained of recurrent UTIs. Conclusion: We revealed that renal impairment may not be associated with MS regarding our finding, but MS could be associated with bladder problems.